Visible light-driven photoelectrocatalytic degradation of acid yellow 17 using Sn 3 O 4 flower-like thin films supported on Ti substrate (Sn 3 O 4 /TiO 2 /Ti) - Huda, A. [UNESP]; Suman, P. H. [UNESP]; Torquato, L. D.M. [UNESP]; Silva, Bianca F. [UNESP]; Handoko, C. T.; Gulo, F.; Zanoni, M. V.B. [UNESP]; Orlandi, M. O. [UNESP] (Elsevier, 2019)
This article reports a new method for preparing mixed valence tin oxide (Sn 3 O 4 ) flower-like nanostructures using a microwave-assisted route. Thin-film Sn 3 O 4 /TiO 2 /Ti electrodes demonstrated highly efficient visible light driven photocatalytic degradation of monoazo acid yellow 17 (AY17) dye, reaching 95% color removal after 60 min at pH 2. Moreover, under low bias potential (0.5 V), the photoelectrocatalytic efficiency increased to 97% color removal and 83% removal of total organic carbon at a kinetic rate almost 3-fold higher than in photocatalysis. Liquid chromatography mass spectrometry was used to identify intermediate formation, and oxidation performance was proposed for photocatalytic and photoelectrocatalytic degradation with no organics identified after 120 min of treatment. The results indicate that Sn 3 O 4 /TiO 2 /Ti photoelectrodes offer a simple, green method for wastewater treatment employing visible light source.
Keywords: Dye degradation; Microwave-assisted hydrothermal synthesis; Photoelectrocatalysis; Sn 3 O 4; Visible-light photocatalysis